Corporate culture in the educational institutions - Корнещук, Вікторія (Pedagogy of Higher and Secondary Education, 2014)
Korneshcuk V. V. Corporate culture in the educational institutions. The article is defined common theoretical foundations of corporate culture and also shown the necessity of her studying and development for ensuring effective activity of institutions including academic. The results of quantitative and qualitative analysis of corporate culture diagnosis conducted on the base of Odessa National Polytechnic University are presented.